The contribution of vehicle-to-grid to balance fluctuating generation: Comparing different battery ageing approaches - David Dallinger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
This paper analyzes how energy throughput and depth of discharge-based battery ageing affects vehicle-to-grid operation of plug-in electric vehicles. Plug-in electric vehicles are discussed as a grid resource to balance the fluctuating electricity generation of renewable energy sources, but their contri-bution to balance fluctuating generation strongly depends on battery ageing and costs to feed back electricity. Therefore, an electricity system scenario with a very high share of wind and solar generation for Germany 2030 is analyzed focusing on different battery cost scenarios and ageing assumptions for plug- in vehicle batteries. The agent-based approach used renders price-based control with vehicle specific dispatch decision possible. Hence, in dependence of the individual state of charge depth of discharge-based battery discharging costs and expected smart charging revenues can be calculated. The results indicate that depth of discharge-based battery ageing results in a more restrictive vehicle-to-grid operation that is substantially affected by the driving behavior. Overall, vehicle-to-grid allows for increasing the contribution to balance fluctuating generation compared to load shifting only but encounters challenges in terms of costs and battery ageing.
urn:nbn:de:0011-n-2776764
Keywords: 330